2015
DOI: 10.1002/lary.25568
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation in children with unilateral hearing loss: A systematic review

Abstract: No firm conclusions can be drawn on the effectiveness of CI in children with UHL, due to heterogeneous findings, small sample sizes, and the lack of high Level of Evidence studies. Based on the findings of this systematic review, cochlear implantation may be an effective treatment option in children with UHL. Laryngoscope, 126:713-721, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 27 publications
0
14
0
5
Order By: Relevance
“…A recent systematic review did not find sufficient high-quality evidence to recommend CI in this population 20 , although there have been individual case series describing significant benefit and high levels of utilization among adults 21 . Additional research should be conducted to determine the role of CI in pediatric UHL.…”
Section: Discussionmentioning
confidence: 97%
“…A recent systematic review did not find sufficient high-quality evidence to recommend CI in this population 20 , although there have been individual case series describing significant benefit and high levels of utilization among adults 21 . Additional research should be conducted to determine the role of CI in pediatric UHL.…”
Section: Discussionmentioning
confidence: 97%
“…A cochlearis implantáció elvégzése indokolt siketséggel határos belsőfül-eredetű sensorineuralis halláscsökkenéskor vagy akár nagy, súlyos fokú cochlearis eredetű halláscsökkenés eseteiben is azoknál a betegeknél, akiknél a beszédértés nem korrigálható megfelelően hagyományos hallásjavító készülékek segítségével [5]. Az utóbbi időben az egyoldali siketség esetén is lehetőségünk van cochlearis implantáció elvégzésére [6]. Nem utolsósorban a belsőfül-malformációval született betegek esetén is szóba jöhet a hallásrehabilitáció az implantáció segítségével [7][8][9].…”
Section: Eredeti Közleményunclassified
“…Az egyoldali siketség döntőrészt a zajos környezetben való beszédértést, a hanglokalizációt befolyásolja, ezáltal pedig negatívan hat az életminőségre [17]. Több tanulmány foglalkozott az egyoldali halláscsökkentek cochlearis implantációval történő rehabilitációjának kimenetelével [6,17,18]. Minden esetben igazolták a vizsgálatok a pozitív kimenetelt, melyet a mi eredményeink is alátámasztanak.…”
Section: Megbeszélésunclassified
“…Children with unilateral hearing loss have been shown to have worse language skills than their siblings with normal hearing [45]. Peters et al conducted a systematic review of 296 articles on cochlear implantation in children with unilateral hearing loss and found mixed results with regards to sound localization and only one study demonstrated improvement in speech and language development [46•]. Most patients had improvements in speech perception in noise, but results were not all statistically significant due to the small sample sizes [46•].…”
Section: Treatmentmentioning
confidence: 99%
“…Peters et al conducted a systematic review of 296 articles on cochlear implantation in children with unilateral hearing loss and found mixed results with regards to sound localization and only one study demonstrated improvement in speech and language development [46•]. Most patients had improvements in speech perception in noise, but results were not all statistically significant due to the small sample sizes [46•]. The role of implantation in single-sided deafness is still an active area of research, both in children and in adults.…”
Section: Treatmentmentioning
confidence: 99%